Isolated Right-Sided Posttraumatic Diaphragmatic Hernia. (19th February 2018) - Amadou Magagi, Ibrahim; Habou, Oumarou; Adamou, Harissou; Adakal, Ousseini; Ali Ada, Mahamoud Omid; Moustapha, Hellé; Abarchi, Habibou
Abstract : Diaphragm is a compliant musculoaponeurotic barrier located between thoracic and abdominal cavities. Traumatic diaphragmatic rupture is a rare clinicopathological entity. We report a case of right-sided posttraumatic hernia in a child following blunt trauma to highlight diagnostic difficulties and therapeutic specific aspects. A 10-year-old boy was admitted to the emergency surgical department with thoracic trauma following pedestrian accident. At admission a haemothorax was suspected and treated by pleural drainage. The diagnosis of a right-sided diaphragmatic rupture was made after computed tomographic scan forty-eight hours later. At surgery, a reduction of herniated abdominal content and a suture of diaphragmatic defect were performed. The postoperative recoveries were uneventful and the patient was followed up for 12 months without symptoms. The possibility of a diaphragmatic rupture should be kept in mind and sought after any trauma of the thoracoabdominal junction as the diagnosis can be challenging in emergency department.